Treuhandanstalt and investment acquisitions: How to ensure that contracts are kept? - Klaus-Dieter Schmidt (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1994)
The process of selling a state-owned company in former centrally planned economies (CPEs) differs greatly from that of buying a private company in western market economies. While a private seller is normally interested in selling his portfolio expensively, a privatizing agency in CPEs has additional goals: she intends to ensure, e.g., that the purchaser continues the company, makes certain investments or maintains a certain number of jobs. Consequently, these concerns are a potential source of conflict. This paper gives an overview of how the German Treuhandanstalt (THA) copes with the problem. It investigates o first what the THA has done in establishing a contractual framework reflecting her social goals and - second how effective this framework has been in realizing them. The results are mixed: the THA has been very successful in putting an investor on the chain. However, she has invested a lot of money. Time must tell whether the results make all these efforts worthwhile.
Keywords: 330; Privatisierung; Übernahme; Vertrag; Neue Bundesländer